Inclusive education: pedagogical approach to online versus face-to-face teaching - Baysan, Aylin; Naeem, Usman (Frontiers in Education, 2023)
In today's educational landscape, active learning is often overlooked during lectures, seminars and tutorials.The aim of this paper is to investigate perceptions of online and face-to face lecture formats and their impact on the learning experiences of undergraduate dental students in Years 3-5. This qualitative study was conducted to investigate the effectiveness of different lecture formats at the Institute of Dentistry for Years 3-5 undergraduate dental students. There were two specific questions asked to dental undergraduate students with additional free text questions. 120 out of 221 undergraduate students participated in this study between October 2019 and February 2020 and only 42 participants included the free text comments.Three core themes related to the blended learning approach were identified: 1) Scheduled versus recorded lectures, 2) Duration of academic lectures, and 3) Neurodiversity and learning experiences. Results showed that the learners perceived the traditional didactic lectures as the least effective format. There is not an "one fits all" lecture format that would accommodate neurodiversity-based approach which focuses on strengths, abilities, and interests of students. Hybrid lecture formats in combination with online teaching coupled with small group tutorials could be suggested. Post-COVID-19 era, there is unique challenge both for the educators and learners due to the lack of clinical practice and heavily relying on the online methods of teaching in Dentistry. Therefore, the implication of these results on planning and financing of programmes could be discussed in Higher Education.